The Impact of Indoles Activating the Aryl Hydrocarbon Receptor on Androgen Receptor Activity in the 22Rv1 Prostate Cancer Cell Line - Zgarbová, Eliška; Vrzal, Radim (International journal of molecular sciences, 2022)
The activation of the aryl hydrocarbon receptor (AhR) by xenobiotic compounds was demonstrated to result in the degradation of the androgen receptor (AR). Since prostate cancer is often dependent on AR, it has become a significant therapeutic target. As a result of the emerging concept of bacterial mimicry, we tested whether compounds with indole scaffolds capable of AhR activation have the potential to restrict AR activity in prostate cancer cells. Altogether, 22 indolic compounds were tested, and all of them activated AhR. However, only eight decreased DHT-induced AR luciferase activity. All indoles, which met the AhR-activating and AR-suppressing criteria, decreased the expression of DHT-inducible AR target genes, specifically KLK3 and FKBP5 mRNAs. The reduced AR binding to the KLK3 promoter was confirmed by a chromatin immunoprecipitation (ChIP) assay. In addition, some indoles significantly decreased AR protein and mRNA level. By using CRISPR/Cas9 AhR knockout technology, no relationship between AhR and AR, measured as target gene expression, was observed. In conclusion, some indoles that activate AhR possess AR-inhibiting activity, which seems to be related to the downregulation of AR expression rather than to AR degradation alone. Moreover, there does not seem to be a clear relationship that would connect AhR activation with AR activity suppression in 22Rv1 cells.
Keywords: nádorové buněčné linie; Indoles; androgenní receptory; prostate cancer; mužské pohlaví; nádory prostaty; Receptors, Aryl Hydrocarbon; Cell Line, Tumor; AR; Receptors, Androgen; Prostatic Neoplasms; Humans; AhR; indoly; receptory aromatických uhlovodíků; skatole; indoles; lidé; Male